Frequency of Congenital Anomalies in Newborns: Congenital Anomalies in Newborns - Ismail, Aksa; Baloch, Falak Naz; Bosan, Rabia; Nazir, Namia; Begum, Amina; Ishaque, Hafiza Mariyam; Kamal, Zareen (Pakistan Journal of Health Sciences, 2025)
Congenital abnormalities (CA) are anatomical or performance-based anomalies that express themselves during the in-utero growth and may be diagnosed during pre-birth, during delivery, and post-birth. Objective: To review the incidence of birth defects in infants. Methods: The descriptive cross-sectional study was conducted in the Department of Obstetrics and Gynecology, Civil Hospital, Karachi, during a period of two years, i.e., March 2017 to March 2019. This study had 213 pregnant women. After birth, there was the identification of congenital anomalies in the newborns by visual examination, and other factors were established by the history of the patient or medical records. All the data were recorded on a pre-determined proforma template. Results: The average age of the participants was 27.381 ± 4.08. The most common congenital anomalies were anencephaly (19.7%), hydrocephalus (15.5%), absence of ear/finger/toe/scrotum/arm/leg/limbs (9.4%), cleft lip and cleft palate (8.9%), meningomyelocele (7%), and talipes (8%). The causal variables were maternal age 30 years and above (20.2%), paternal age 35 years and above (19.7%), maternal diabetes mellitus (20.2%), consanguinity marriage (20.2%), maternal infection during pregnancy (8.9%), and maternal folic acid supplementation (61.5%). These are said to be descriptive and not causal. Conclusions: This study highlights the rate of congenital anomalies and the types of congenital anomalies. Its results touch on the importance of routine antenatal care and prenatal screening to intervene and manage affected pregnancies at an earlier stage.